PEMBANGUNAN REHABILITASI RUMAH TIDAK LAYAK HUNI TERMASUK JAMBAN/ SANITASI KELURAGA OLEH PEMERINTAH DAERAH KABUPATEN KARIMUN DI KECAMATAN TEBING TAHUN 2012 - Ruvi Indayu; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research on the development of uninhabitable housing rehabilitation, in this case in the Tebing District Karimun Regency to poor households is important to do, because the house is one of the basic human needs to be met, not only has the physical function, namely as a place of refuge but also has strategic value as the center of activities in which to implement its functions, especially the function of the children's education and coaching members of his family. Based on that, each family has always sought to have decent housing, even though objectively the whole family can not fulfill his desire. This was due to several factors, mainly economic factors family because of poverty and about the function of the house itself. This research aims to see about the implementation of the development activities uninhabitable housing rehabilitation including latrines/ sanitation family and factors that hinder the implementation of development activities uninhabitable housing rehabilitation including latrines/ sanitation family by Local Government Karimun Regency in Tebing District in 2012.This research was conducted using a qualitative approach. Techniques used in data collection are interviews, documentation and observation. The primary data source is obtained from the beneficiers, social services officials, DPRD, the companion, districts officials, and village officials. Sources of secondary data obtained from the reports, official documents, archives and other data as well as a complement of the primary data.The results of this research showed that the implementation of development activities uninhabitable housing rehabilitation can be said to run well. Because most beneficiaries have been able to feel the benefits and this activity has a positive impact on meeting the needs of the home, social and psychological conditions although in practice there is still a shortage. The factors that hinder the implementation is one of the building material supply delays, because the manager is less responsible for his work. By looking at the problems that occur are expected to Local Government must be responsive, coordinate with other Government agencies and to the future implementation of the rehabilitation RTLH still need to be optimized with regard to strengthening the executive team, and the amount of the disbursement of funds, management team, and synergy with the various sectors.Keywords: House, Development, Rehabilitation RTLH